How Can Social Emotional Learning Strategies with Mindfulness Techniques Improve Reading Literacy? - Viantho, Indriana; Nirmala, Sri Dewi (Universitas Pendidikan Ganesha, 2024)
According to national and international studies, students’ literacy in Indonesia performed in a low level. Given the literacy conditions of students in Indonesia, as described above, teachers play a crucial role in preparing students for the future, considering that importance of literacy skills in the 21st century. Therefore, this study aims to analyze how social emotional learning strategies using mindfulness techniques, namely the